2014
DOI: 10.1053/j.gastro.2014.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Produce Interleukin 6 and Signal via STAT3 to Promote Expansion of Human Hepatocellular Carcinoma Stem Cells

Abstract: Background & Aims Cancer stem cells (CSCs) can contribute to hepatocellular carcinoma (HCC) progression and recurrence following therapy. The presence of tumor-associated macrophages (TAMs) in patients with HCC is associated with poor outcomes. It is not clear whether TAMs interact with CSCs during HCC development. We investigated whether TAMs affect the activities of CSCs in the microenvironment of human HCCs. Methods HCCs were collected from 17 patients during surgical resection and single cell suspensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
467
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 570 publications
(515 citation statements)
references
References 40 publications
17
467
1
Order By: Relevance
“…However, we still could not exclude other mechanisms by which MDSCs or macrophages contribute to tumor growth. For example, MDSCs and macrophages were recently reported to promote cancer stemness (35,36). We also confirmed it by showing that coculture of MSDCs enhanced the expression of stemness-related genes of Hepa1-6 cells and their proliferation.…”
Section: Fap þsupporting
confidence: 77%
“…However, we still could not exclude other mechanisms by which MDSCs or macrophages contribute to tumor growth. For example, MDSCs and macrophages were recently reported to promote cancer stemness (35,36). We also confirmed it by showing that coculture of MSDCs enhanced the expression of stemness-related genes of Hepa1-6 cells and their proliferation.…”
Section: Fap þsupporting
confidence: 77%
“…In pancreatic tumors, TAM depletion arrests the proliferation of tumor-initiating cells (95). Indeed, TAMs can sustain CSC proliferation by releasing proinflammatory cytokines such as TNF-α and IL-6, which reinforce tumor cell proliferation through NF-κB and STAT3 signaling pathways (96,97). These same molecular pathways may be activated through a direct TAM-to-CSC contact via CD90 and ephrin A4 receptors (98).…”
Section: Mdsc-and Tam-dependent Protumoral Aidmentioning
confidence: 99%
“…And in fact a recent study showed that tumor-associated macrophages (TAMs) promote the expansion of CSCs in HCC. Tocilizumab is a recently FDA approved drug that targets IL-6 receptor, and treatment of HCC cells with tocilizumab or STAT3 knockdown reduced the ability of TAMs to not only promote CSC expansion but also growth of xenograft tumors (8). Thus, STAT3 signaling appears to be a promising therapeutic target for HCC treatment.…”
mentioning
confidence: 99%